Effect of community participation on primary health care - Gammanpila , U.P (My University, 1997)
This descriptive cross-sectional study is carried out to evaluate the programme’s effect on the primary health care of the area, as well as assess the extent of community participation gained through the programme . The health indicators were analyzed to compare the health status before and after the programme and showed a significant improvement in maternal health care, child health care, environmental health care and control of communicable disease indicators showing the programme’s positive impact on the health care status of the population concerned